Impact of Destination Image and Satisfaction on Word of Mouth Communication of Tourists in Sri Lanka - Jayarathne, P.G.S.A. (Scholar Commons, 2018)
Word of mouth communication, country image and destination satisfaction have been identified as significant aspects in tourist industry today more than any other time as tourists make reviews on internet based on such reviews influence the prospective tourists’ behaviour. Although scholars have scrutinized in this area they are mainly limited to developed countries reflecting a gap in the literature to explore the insights in the developing countries context. Addressing such gap in the literature, this study aims to examine the impact of country image and destination satisfaction of tourists on their word of mouth communication in Sri Lanka. A survey is carried out with 354 tourists in Sri Lanka. The result uncovers that the destination satisfaction fully mediates the relationship between country image and word of mouth communication of tourists in Sri Lanka. Finally, the paper makes important implications and suggestions for practitioners as well as for academics in the field of tourism.
Keywords: country image, destination satisfaction and word of mouth communication, tourism industry